What is the Most Important Issue in Indonesia’s Political Belief System? Network Analysis of Attitude and Voting Behavior in 2014 and 2019 - Hasan, Khaerullah Fadhli Arasy; Yustisia, Whinda; Milla, Mirra Noor; Brandt, Mark (Makara Human Behavior Studies in Asia, 2025)
Previous research has shown that attitudes toward political issues have a significant influence on voting behavior (Bukari et al., 2022). However, not all issues exert equal influence, and some may have a more direct impact on voting behavior than others. This study applies network analysis within the framework of the PBS model (Brandt & Sleegers, 2021) to explore the issues that most strongly shaped voters’ choices in Indonesia’s 2014 and 2019 elections. To answer the research question, we used data from a national survey (n = 962) conducted in 2018. The analysis was conducted by evaluating the shortest path values based on mixed graphical models to estimate the strength of the relationship between attitudes toward 12 issues and the choice of political party and president. The results show that issues in the religion dimension, particularly the belief that leaders should be of the same faith and religion, consistently had a direct and shortest path with the presidential choice in both election periods (2014 election ≈ 0.03; 2019 election ≈ 0.009–0.05). At the dimension level, ANOVA analysis also shows that the shortest path between attitudes toward issues and presidential choice is significantly different across the three dimensions in both the 2014 (F(2, 9) = 8.16, p < 0.01) and 2019 (F(2, 9) = 21.31, p < 0.001) elections. Specifically, we found that the religious dimension was more closely related to voting behavior than the other dimensions. This finding was replicated in the choice of political party but only in the upcoming election and not in the previous election. Therefore, we can conclude that religious issues play a more important role in Indonesia’s political choice.